2017
DOI: 10.31887/dcns.2017.19.1/fdacquisto
|View full text |Cite
|
Sign up to set email alerts
|

Affective immunology: where emotions and the immune response converge

Abstract: Affect and emotion are defined as “an essential part of the process of an organism's interaction with stimuli.” Similar to affect, the immune response is the “tool” the body uses to interact with the external environment. Thanks to the emotional and immunological response, we learn to distinguish between what we like and what we do not like, to counteract a broad range of challenges, and to adjust to the environment we are living in. Recent compelling evidence has shown that the emotional and immunological sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(25 citation statements)
references
References 133 publications
(118 reference statements)
0
21
0
4
Order By: Relevance
“…3 B). Studies showed that inflammatory responses was involved in the emotional disorder and neuropathic pain [ 39 , 40 ]. From these six terms, we selected seven upregulated target genes including S100a9 , Ltf , Slip , Cd244 , Acp5 , Areg and Six1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3 B). Studies showed that inflammatory responses was involved in the emotional disorder and neuropathic pain [ 39 , 40 ]. From these six terms, we selected seven upregulated target genes including S100a9 , Ltf , Slip , Cd244 , Acp5 , Areg and Six1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In human medicine, the relatively new interdisciplinary field of Affective Immunology studies the links between emotion and the immune system. This covers both the way the immune system affects the emotional state and also the way that emotions alter the status of the immune status ( 7 , 18 ). Studies investigating these links in humans use different approaches and constructs, making it difficult to interpret results and draw conclusions for non-human species.…”
Section: Wellbeing and Health—evidence In Humansmentioning
confidence: 99%
“…Given the complexity of these immune reactions and their interactions with both the gut microbiome and the emotions, there are also many different ways in which immunity can affect and be affected by emotional state ( 10 , 58 ). First, changes in the immune system, such as inflammation, may directly affect, and be affected by, the emotional state ( 7 , 13 , 59 ). Second, immunity and emotional state may be linked by more indirect routes, for example, via effects on the cardiovascular system (e.g., ( 8 , 13 , 60 ) and the gut microbiome ( 61 ).…”
Section: Wellbeing and Health—what We Still Need To Knowmentioning
confidence: 99%
See 1 more Smart Citation
“…To understand the dynamics of the fine interaction between the emotion (or affection) and immune response, a specialized branch called “affective immunology” was recently introduced to distinguish it from “psychoneuroimmunology” which broadly studies the relationship between psychological processes, neuroendocrine activities, and immune systems ( 7 ). The high plasticity of the immune system significantly raises the exciting possibility of translational research.…”
Section: Introductionmentioning
confidence: 99%